H. D. Thoreau´s Prose in Czech Translations - Strašková, Jana (Univerzita Pardubice, 2012)
The bachelor paper deals with the topic of Transcendentalism and Thoreau, as he was its representative. His famous book Walden, precisely only one chapter, was chosen in order to be analyzed. This writing was translated by Seifert (1933), Franta (1949) and Schwarz (1991). These three translations are compared in the practical part where the author evaluates and comments on the differences. The main sources for evaluation are the books written by Levý who deals with the art of translation. The finding will be summarised in a relevant conclusion.
Prózy H. D. Thoreaua v českých překladech
Keywords: Amerika; Thoreau, Henry David; transcendentalismus; příroda; překlad; porovnání; analýza; America; transcendentalism; nature; translation; comparison; analysis